Integrative expression vectors for overexpression of xylitol dehydrogenase (XYL2) in Osmotolerant yeast, Candida glycerinogenes WL2002-5. (1st January 2015) - Zhang, Cheng; Zong, Hong; Zhuge, Bin; Lu, Xinyao; Fang, Huiying; Zhuge, Jian
Abstract: Yeasts are excellent hosts for the production of recombinant proteins. Candida glycerinogenes WL2002-5, an osmotolerant yeast with extremely high glycerol productivity, provides an attractive eukaryotic expression platform. The integrative vectors PURGAP- gfp and PURGPD- gfp harbouring phleomycin-resistance coding sequence and GFP coding sequence with P CgGAP, P CgGPD promoter, respectively, were constructed. The recombinant plasmid PURPpGAP- gfp with the promoter P PpGAP based on the sequence of Pichia pastoris GAPDH gene and the plasmid PURScGAP- gfp with the promoter P ScGAP from Saccharomyces cerevisiae were constructed. After transformation, the copy number of gfp gene, which determined using fluorescent quantitative real-time polymerase chain reaction (FQ-RTPCR) in genome of C. glycerinogenes is 1. Expressions of gfp at different levels were conducted using different promoters by osmotic stress containing NaCl or glucose for the recombinant strains. In this study, C. glycerinogenes WL2002-5, expressing xylitol dehydrogenase ( XYL2 ) gene from Pichia stipitis, has the ability to produce glycerol from xylose entered into pentose phosphate pathway. Two recombinant strains of PURGAPX, PURGPDX with XYL2 overexpression were constructed to ferment a mixture of glucose and xylose simultaneously in batch fermentation. Compared to C. glycerinogenes WL2002-5 strain, glycerol production from xylose in strains PURGAPX, PURGPDX were increased by 95.9 and 121.1 %, respectively.